Analysis of Λ b 0 → pK − μ + μ − decays - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adefisoye, AA; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; et al. (Springer, 2024)
The differential branching fraction and angular coefficients of Λb0 → pK−μ+μ− decays are measured in bins of the dimuon mass squared and dihadron mass. The analysis is performed using a data set corresponding to 9 fb−1 of integrated luminosity collected with the LHCb detector between 2011 and 2018. The data are consistent with receiving contributions from a mixture of Λ resonances with different spin-parity quantum numbers. The angular coefficients show a pattern of vector-axial vector interference that is a characteristic of the type of flavour-changing neutral-current transition relevant for these decays.